Seasonal Variability and Prediction of Cotton Output in Tamil Nadu (International Journal of Food and Nutritional Sciences, 2022)
An important player in India's cotton production landscape, Tamil Nadu is the focus of this investigation into the seasonal variability and forecasting of cotton output. This research intends to shed light on the seasonal variations and their effects on cotton production by evaluating historical data and taking into account a wide range of significant elements, such as meteorological fluctuations, soil conditions, and agricultural techniques. The research, which makes use of cutting-edge statistical methods and forecasting models, highlights the importance of grasping the complexities of seasonal patterns and their effects on cotton production. This study sheds light on the relationship between seasonal variability and cotton output by an in-depth examination of seasonal trends, including elements like rainfall patterns, temperature variances, and planting seasons. The results of this study provide important insights for farmers, policymakers, and other stakeholders, paving the way for better decision-making and the creation of flexible plans to increase cotton production in Tamil Nadu in a way that is both environmentally and economically sustainable.